Andrographolide Derivative AL-1 Ameliorates Dextran Sodium Sulfate-Induced Murine Colitis by Inhibiting NF-κB and MAPK Signaling Pathways. (7th October 2019) - Jing, Mei; Wang, Yuqiang; Xu, Lipeng
Abstract : Trinitrobenzenesulfonic acid (TNBS) and dextran sodium sulfate (DSS) are commonly used to induce experimental murine ulcerative colitis (UC). Our recent study has demonstrated that a novel andrographolide derivative, AL-1, ameliorated TNBS-induced colitis in mice. However, the effect of AL-1 on DSS-induced murine colitis and the underlying mechanisms are yet unknown. In the present study, we aimed to investigate the therapeutic potential of AL-1 against DSS-induced UC in mice and to define its mechanisms of action. Oral administration of AL-1 attenuated body weight loss, reduced colon length shortening, lowered the disease activity index score, and alleviated colon histological damage. AL-1 significantly inhibited myeloperoxidase activity and suppressed immune inflammatory responses in colonic tissues. Moreover, AL-1 reversed DSS-altered expression of inflammatory cytokines in DSS-induced colitis mice. Importantly, the efficacy of 45 mg/kg of AL-1 was higher than that of 100 mg/kg of the positive control drugs 5-aminosalicylic acid and mesalazine. AL-1 decreased lipopolysaccharide-induced generation of reactive oxygen species and nitric oxide in cultured macrophages in vitro; it also reversed the altered expression of inflammatory cytokines. In both in vivo and in vitro studies, Western blot analysis revealed that AL-1 reduced the expression of phosphorylated NF- κ B p65 and I κ B α, downregulated the expression of iNOS and COX-2, and attenuated the expression of phosphorylated p38 mitogen-activated protein kinase (MAPK), ERK, and JNK. In conclusion, AL-1 alleviated DSS-induced murine colitis by inhibiting activation of the NF- κ B and MAPK signaling pathways. Our data suggest that AL-1 could be a potential new treatment for UC.